Innovative potential as a component of development of the economy of the country - Gliznutsa, M. Yu. (My University, 2019)
The article is devoted to topical problems of evaluation and management of innovative development of the state at the regional level due to the formation of the components of the state innovative capacity assessment. Analyzed the objective conditions and causes of the problem situations in the economy and set objectives to ensure intellectual resource of the process of development of economic systems. The directions of development of innovative potential of Ukraine and its regions are taken into account, taking into account foreign experience, which made it possible to offer basic approaches to improving methodological support of identification of the current state of innovative potential of economic systems of state and regional levels of government.
Keywords: innovative potential; economic systems; regions